Exploring pain and suffering through spatial acousmatic music: innovative perspectives beyond conventional music therapy - Stavropoulos, Nikos; Johnson, Mark I. (Frontiers in Pain Research, 2025)
In this perspective article we contend that acousmatic music, which departs from the traditional “instrumental music paradigm” by obscuring or removing the origin of sounds, may deepen a person's understanding and expression of pain and suffering, offering therapeutic potential. We propose that intentional engagement with acousmatic music can reshape listening habits, articulate and reframe the meaning of bodily and emotional experiences, and alleviate distressing sensations, feelings and thoughts. We propose that acousmatic music evokes memories of previous psychological traumas, such as painful events, and by doing so can prompt listeners to curiously explore the meaning and purpose of distressing symptoms. We argue that creative engagement with acousmatic music may allow individuals to express their somatic, emotional, and cognitive experiences, potentially leading to a deeper understanding of their living experiences. We discuss future directions for research and practice. We offer readers a stereo reduction excerpt of acousmatic music to facilitate an appreciation of the unusual nature of acousmatic music composition (https://soundcloud.com/nikos-stavropoulos/topophilia).